2011
DOI: 10.1111/j.1365-2966.2011.18611.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodicities in the coronal rotation and sunspot numbers

Abstract: The present study is an attempt to investigate the long term variations in coronal rotation by analyzing the time series of the solar radio emission data at 2.8 GHz frequency for the period 1947 - 2009. Here, daily adjusted radio flux (known as Penticton flux) data are used. The autocorrelation analysis shows that the rotation period varies between 19.0 to 29.5 sidereal days (mean sidereal rotation period is 24.3 days). This variation in the coronal rotation period shows evidence of two components in the varia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
41
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 37 publications
4
41
0
Order By: Relevance
“…Various frequencies correspond to various altitudes in the solar corona and different methods have been used (e.g., the Sun analysed as a star with no latitudinal dependence, autocorrelation analysis with a time lag, etc.). However, it seems that up to now either a very weak or no correlation between the coronal rotational period and the sunspot activity can be verified Chandra & Vats 2011). This result refers to the height of about 60 000 km and the observing frequency of 2.8 GHz.…”
Section: Introductionmentioning
confidence: 89%
“…Various frequencies correspond to various altitudes in the solar corona and different methods have been used (e.g., the Sun analysed as a star with no latitudinal dependence, autocorrelation analysis with a time lag, etc.). However, it seems that up to now either a very weak or no correlation between the coronal rotational period and the sunspot activity can be verified Chandra & Vats 2011). This result refers to the height of about 60 000 km and the observing frequency of 2.8 GHz.…”
Section: Introductionmentioning
confidence: 89%
“…Coronal differential rotation has been also investigated by white light, soft X‐ray, ultraviolet (UV) rays, radio, and so on (Chandra & Vats 2011). Studies of the white‐light corona show a radially rigid rotation in the corona.…”
Section: Introductionmentioning
confidence: 99%
“…Satellite observations allow us to study the coronal differential rotation using soft X‐ray and UV rays. Some authors have shown that there is an almost rigid corona in soft X‐ray and UV rays, or a shallower rotation profile of the corona that varies with latitudes unlike at the lower atmosphere (Timothy, Krieger & Vaiana 1975; Weber, Alexander & Acton 1997; Weber et al 1999; Chandra, Vats & Iyer 2010; Chandra & Vats 2011; Vats & Chandra 2011). However, others have obtained contrasting results (Brajs̆a et al 2002, 2004; Karachik et al 2006; Zaatri et al 2009; Wöhl et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations